Authentication of Jamu from Paracetamol Adulteration Using Thin-Layer Chromatography And UV-Vis Spectrophotometry - Mamay Maslahat; Reggiana Nurul Ikhsani Sandy; Srikandi (Sains Natural: Journal of Biology and Chemistry, 2026)
The distribution of herbal medicines containing chemical substances (BKO) that are dangerous for the public is prohibited based on the Regulation of the Minister of Health of the Republic of Indonesia No. 007 of 2012, however, they are still often found in the community. The types of BKO found in herbal medicines for aches and pains include dexamethasone, phenylbutazone and paracetamol. Paracetamol is an active substance used in modern medicine that has analgesic and antipyretic properties, so it can relieve pain in certain doses. Paracetamol in herbal medicines can be identified qualitatively using thin layer chromatography (TLC) with a standard paracetamol reference solution that has an Rf value of 0.77 with a mobile phase of ethyl acetate-ethanol-ammonia (85:10:5, v/v), and a UV-Vis Spectrophotometer. Therefore, authentication of herbal medicines in circulation is needed as a guarantee of safety to the public. The purpose of this study was to detect BKO paracetamol in herbal medicines for aches and pains qualitatively and quantitatively using TLC and a UV-Vis spectrophotometer. The research stages included sampling herbal medicine from three industrial areas, namely Sentul, Cakung, and Cikarang with the types of herbal medicine selected being packaged and bulk as well as powder and liquid forms; identification of paracetamol using TLC; and analysis of paracetamol using a UV-Vis Spectrophotometer. Based on the TLC analysis, it was found that 3 out of 24 samples of herbal medicine for aches and pains were positive for containing paracetamol. The three samples were obtained from the Cikarang Industrial Area with liquid preparations from branded and bulk packaging types with the codes C1Xl, C2Xl, and C2Yl. The paracetamol concentrations in these samples were 3.8417; 2.1390; and 15.1980 mg/L, respectively.